HUBUNGAN PELAKSANAAN KOMUNIKASI TERAPEUTIK DENGAN TINGKAT KECEMASAN AKIBAT HOSPITALISASI PADA ANAK USIA SEKOLAH YANG DIRAWAT DI RSUD KAYUAGUNG TAHUN 2017 - Mareta Akhriansyah (Universitas Batanghari Jambi, 2018)
Anxiety is a confused worries and expanding, which is related beetween uncertainly and unpowerless. Anxiety will uppear as responce by stressor, for both phisical stressor and psycological stressor which can make un city till depression level of children. An also the effect of it is denial from the children to get any hospital treatment. Communication can reduce children anxiety hospitalized. The aim of this study was to know and influence of relationship beetween therapeutic communication implementation with anxiety level of school-age children while hospitalization.This study used correlation study, the sample is taking by quota sampling technique with 40 respondens. Anxiety level quesioner of children while hospitalized by Hamilton Rate Scale for Anxiety (HRS-A). Data analysis are using chi square (x2) formula. The result showed that therapeutic communication is influence to decrease a level of anxiety school-age children hospitalized (p=0,006 <α=0.05). Nurse will be increasing therapeutic communication in every nursing treatment with children while hospitalized and also included their parents into their nursing treatments. Key word : Anxiety hospitalized, therapeutic, communication